The normal cardiogenesis and after some teratogens treatment. - Kozlov V.O.; Shatorna V.F.; Mashtalir M.A. (Морфологія, 2007)
The analysis and comparison of the our experimental results and the data of other researchers about the stages of normal and abnormal cardiogenesis under the influence of hypotermia, hypoxia, ethanol, retinoic acid were made. The common retardation of embryonic development is the most often case after teratogens factor treatment as well as the delay in interventricular and intaratrial septa development, not complete closure of interventricular foramen, abnormal development of the heart wall and endocardial cushions in all chambers of the embryonic heart. The altering of the basic cardiogenic processes caused the abnormal development of atrioventricular valves as well as aortic and pulmonary trunk valves in most embryos. The spectrum of heart defects including defect of interventricular septum, double outlet of right ventricle and complete transposition of great vessels was observed. Our data suggest that the neural crest cell play a role in the abnormal heart development. The abnormal flexio and torsio of the embryo, the malformation of the cranial portion of embryo, the cardiac ectopia and umbilical herniation among external abnormalities were also observed.